Profiling Of Journalists in Balochistan: An Exploratory Study - Shairzaman Kakar; Prof. Dr. Muhammad Zafar Iqbal; Shafquat Ali Chachar; Sohaib Saleh (Social Science Review Archives, 2025)
In the today digital age, the journalists face real threats around the world particularly in Pakistan, which is badly affected the freedom of expression and human rights. They lose their status due the different environmental factors. The current analysis explores the profiling of the journalists in Balochistan as an exploratory study. The researcher used quantitative technique on the population of different districts of Balochistan (Zhob, Musakhail, Chaman, Ziarat, Nushki, Jaffarabad, Gwadar, and Awaran). The data has been collected though survey method form 300 working full time, part time and free-lancing journalists on the basis of systematic sample technique, using manual questionnaire consisting different scale questions. After the collection, the data was analyzed by statistical package of social sciences (SPSS) to tabulate the data with the categories, frequencies and percentage for batter understanding and real result. The researcher found out that the journalism in Balochistan deter the journalists form viewing journalism as a secure and alternative career. The journalist faces extreme threats consist of harassment, intimidation and physical violence form both state and non-state actors, making their profession highly perilous. Limited institutional support, lack of security measure and constant fear for personal security further exacerbate the risk, different effecting their ability to work independently and ethically. The current study suggested that the government should develop journalist protection policies, Press clubs & media organization, Ensure independent journalism for the resilient profile of journalist in Balochistan.